Legal Review of The Judge’s Dissenting Opinion Regarding the Age Limit for Presidential Candidates and Vice-Presidential Candidates in Constitutional Court Decision Number 90/Puu-XXI/2023 - Safe’i, Abdulah; Pahlevi Dalimunthe, Reza; Dinul Faqih, Moch.; Nisa Syafithri, Firda (Yayasan Mentari Madani, 2024)
The Constitutional Court has handed down a decision regarding the age limit for presidential and vice presidential candidates on October 16, 2023, namely decision Number 90/PUU/XII/2023. This decision will take effect in 2024 and has permanent legal force so that its implementation will have an impact on all Indonesian citizens, including Gibran Rakabuming Raka, who are under 40 years old and can nominate as presidential/vice presidential candidates. This gave rise to pros and cons among academics and society because the chairman of the Constitutional Court at that time was Anwar Usman, who is the family of Gibran Rakabuming Raka. However, in the Constitutional Court's decision there were differences of opinion or dissenting opinions among the judges handling the case. This research aims to find out how the judge's dissenting opinion occurred in the decision and what the legal consequences of the decision will be after it has permanent legal force if it contains formal defects or violations of the judge's code of ethics because it contains an element of interest. The method used in this research is normative juridical using a case approach and a statutory approach. The results of this research are that dissenting opinions can be an alternative correction for errors in court decision making. The majority vote of judges is considered fair if the decision is clear, but this does not necessarily mean that the decision is completely correct. The legal consequences of the decision of the Constitutional Court Number 90/PUU-XXI/2023 remain final and have permanent legal force, even though the process that occurs during the trial process in a case at the Constitutional Court, whether there are defects or violations of the code of ethics, does not affect the decision that has been determined because it is absolute or inkrah. And the violation of the judge's code of ethics in the Constitutional Court Decision Number: 90/PUU-XXI/2023 concerning the age limit for presidential and vice-presidential candidates does not affect the validity of the decision, which means the decision is final, must continue to be implemented in accordance with existing provisions